An Analysis of the Impact of Abolition the Parliamentary Threshold on Democracy in Indonesia - Muhammad Taufik Qurahman; Achmad Nurmandi; Helen Dian Fridayani (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The abolition of the parliamentary threshold has certainly created pros and cons. This policy shows the dynamics in Indonesian politics, it certainly changes the implementation of significant changes in the Indonesian democratic system and of course also has an impact that can affect democracy in Indonesia. Therefore, the question is how this policy is relevant to the quality of democracy in Indonesia. This research uses a descriptive qualitative research method. The collection technique used in this research is qualitative by relying on secondary data sources. Data sources come from mass media and also previous studies that are relevant to the topic discussed. The results of the research based on mapping from the mass media using two indicators show that the wide participation indicator with its parameters, namely reducing wasted votes, is the biggest impact that can be caused by removing regulations regarding the parliamentary threshold. With the results showing that the wide participation indicator is the most influential impact that can be caused by the elimination of the parliamentary threshold, this is certainly a good impact on democracy in Indonesia because it can make political participation and diversity of representation in parliament increase, and make fewer votes wasted because they do not reach the threshold, which of course also affects the improvement of the quality of democracy in Indonesia.